Zika in the Brain: New Models Shed Light on Viral Infection - Hickman, Heather D. (Trends Mol Med, 2016)
The current Zika virus (ZIKV) outbreak is associated with high numbers of human congenital birth defects, yet it is unclear how ZIKV infection during pregnancy causes these abnormalities. Three new mouse models now show that ZIKV crosses the placenta and replicates in the brains of fetal mice.